2022
DOI: 10.1101/2022.09.12.507590
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Corollary Discharge Circuit in Human Speech

Abstract: When we vocalize, our brain distinguishes self-generated sounds from external ones. A corollary discharge signal supports this function in animals, however, in humans its exact origin and temporal dynamics remain unknown. We report Electrocorticographic (ECoG) recordings in neurosurgical patients and a novel connectivity approach revealing major neural communications. We find a reproducible source for corollary discharge across multiple speech production paradigms localized to ventral speech motor cortex befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…During music listening, this gradient is organized around the left sensorimotor cortex, a hub implicated in feedback signaling during auditory perception (19,41). This region might correspond to area 55b, a proposed keystone of sensorimotor integration critical in both music (42) and speech (43,44) perception. This hub coordinates ventral delta (1.4 Hz) and dorsal beta (20-30 Hz) intrinsic neural dynamics and is hence constitutive of the emergence of audio-motor coupling.…”
Section: Discussionmentioning
confidence: 99%
“…During music listening, this gradient is organized around the left sensorimotor cortex, a hub implicated in feedback signaling during auditory perception (19,41). This region might correspond to area 55b, a proposed keystone of sensorimotor integration critical in both music (42) and speech (43,44) perception. This hub coordinates ventral delta (1.4 Hz) and dorsal beta (20-30 Hz) intrinsic neural dynamics and is hence constitutive of the emergence of audio-motor coupling.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that several studies implicate ventral precentral gyrus more strongly than its rostral neighbor IFO in driving suppression and causing compensatory movements during speech. Connectivity analyses of human electrocorticography (ECoG) identified the ventral precentral gyrus as a source of the corollary-discharge signal, peaking prior to articulation and targeting STG (Khalilian-Gourtani et al, 2022). In that study, activity in inferior frontal gyrus preceded activity in precentral gyrus, but the stronger correlate of a motor-to-auditory discharge arose from precentral gyrus.…”
Section: Discussionmentioning
confidence: 99%
“…This claim is also supported by research linking deficits in auditory-verbal short-term memory to supramarginal gyrus. 24 Furthermore, multiple studies have shown efference copy in temporal regions, 25,26 a process by which motor regions inform auditory areas of planned outgoing motor commands. Thus, this link between motor and auditory areas might explain the similar latencies observed between sensorimotor cortex and STG.…”
Section: Discussionmentioning
confidence: 99%